Pemberdayaan Santripreneur di Pesantren: Kajian Kepemimpinan Perempuan (Nyai) dalam Meningkatkan Keterlibatan Santriwati dalam Berwirausaha - Ratih Pratiwi; Windi Novia Ratri Wardhani; Shidqon Prabowo; Farikhah Amaniyah; Fatkhur Rohim (Universitas Islam Negeri Alauddin Makassar, 2022)
Pesantren is basically an institution that plays a very important role in the era of globalization, namely shaping one's personality. Character education in the current era of globalization really needs character education, because the purpose of character education is to expand spiritual intelligence. The biggest challenge in facing globalization and modernization is where the empowerment of human resources (HR) and the economy in life has changed in every way, especially social and socio-cultural which is very fast and fundamental in every aspect of life. Islamic boarding schools must be able to create people who are IMTAQ (faithful and pious), who are knowledgeable and charitable and form modern humans who are sensitive to contemporary social realities such as